Corrosion Inhibitory Properties of Eucalyptus camaldulensis (red gum) Leaves Extract on Iron in Acidic Media (Damak Campus Journal, 2025)
The corrosion inhibition process is a complex phenomenon, and if one uses a plant extract, then the complexity increases several times. The plant extract contains different kinds of phytochemicals, and they may interact with the metal surface through some organometallic complex formation, which is responsible for the inhibition effect.The aqueous extract of leaves of Eucalyptus camaldulensis (red gum)was tested for corrosion inhibition on the iron in 1M, 2M & 4M hydrochloric acid solutions at 30°C using the weight loss technique. The data obtained by weight loss measurement revealed that the leaf extract has a good inhibitory nature and mitigates the rate of corrosion. Inhibition efficiency increases with increasing inhibitor concentration, and after a certain concentration, efficiency decreases.